2009
DOI: 10.1038/jhg.2009.118
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism located in TCRA locus confers susceptibility to essential hypersomnia with HLA-DRB1*1501-DQB1*0602 haplotype

Abstract: Essential hypersomnia (EHS) exhibits excessive daytime sleepiness without cataplexy and is associated with the HLA-DRB1*1501-DQB1*0602 haplotype, similar to narcolepsy with cataplexy. Single-nucleotide polymorphism (SNP) rs1154155 located in the T-cell receptor a (TCRA) locus has been recently identified as a novel genetic marker of susceptibility for narcolepsy with cataplexy. We investigated whether the SNP was associated with EHS in the Japanese population. We found a significant association with EHS patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…Several previous studies reported the possibility that EHS is not homogeneous and HLA-DRB1*1501-DQB1*0602 haplotype-positive EHS is essentially different from haplotype-negative EHS (Honda et al 1998;Miyagawa et al 2009Miyagawa et al , 2010. Thus, EHS cases were subdivided into two groups, HLA-DRB1*1501-DQB1*0602 haplotype-positive and -negative EHS, for stratified analysis.…”
Section: Analysis Of Ehs Samplesmentioning
confidence: 98%
See 2 more Smart Citations
“…Several previous studies reported the possibility that EHS is not homogeneous and HLA-DRB1*1501-DQB1*0602 haplotype-positive EHS is essentially different from haplotype-negative EHS (Honda et al 1998;Miyagawa et al 2009Miyagawa et al , 2010. Thus, EHS cases were subdivided into two groups, HLA-DRB1*1501-DQB1*0602 haplotype-positive and -negative EHS, for stratified analysis.…”
Section: Analysis Of Ehs Samplesmentioning
confidence: 98%
“…The significant association of SNP rs8119787 was observed again in HLA-positive EHS (P = 0.032; OR = 1.46; 95% CI = 0.98-2.17) ( Table 3). In addition, we focused on the idea that the previous studies suggested that HLA-positive EHS exhibits autoimmune pathogenesis, similar to narcolepsy (Honda et al 1998;Miyagawa et al 2010). NFATC2 is an immune-related gene and plays a role in the inducible expression of cytokine genes in T cells.…”
Section: Analysis Of Ehs Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Recent genome-wide association studies of HLA-DQB1*0602-positive European Caucasians, healthy Americans, and narcoleptics with cataplexy have identified the existence of a polymorphism in the T-cell receptor alpha (TRA) gene. 16,17 The TRA gene encodes a protein that activates cytotoxic CD8 cells and CD4 helper cells, resulting in susceptibility to the destruction of hypocretinergic HLA-DQB1*0602-positive cells. 16,17 These results suggest that narcolepsy is an autoimmune disease with HLA haplotype and a TRA polymorphism as risk factors.…”
Section: Genetics Of Narcolepsymentioning
confidence: 99%
“…16,17 The TRA gene encodes a protein that activates cytotoxic CD8 cells and CD4 helper cells, resulting in susceptibility to the destruction of hypocretinergic HLA-DQB1*0602-positive cells. 16,17 These results suggest that narcolepsy is an autoimmune disease with HLA haplotype and a TRA polymorphism as risk factors.…”
Section: Genetics Of Narcolepsymentioning
confidence: 99%